Evaluation of Steel Frame Equipped with the Replaceable Shear Link Made of Shape Memory Alloy under the Impact Load - Reza Kamgar; Seyed Ali Mahmoudy; Roham Zakavi (Journal of Rehabilitation in Civil Engineering)
Despite their low stiffness, moment frames (MFs) are considered conventional lateral strength systems for low- and moderate-rise structures due to their ability to absorb energy and provide suitable ductility, along with architectural considerations. In return, a framed tube system with deep beams and short spans suits the high-rise structures. Due to the differences between the span length-to-depth ratios of the beams in this structural system, the regulations for MFs cannot apply to them. Moreover, a low value for the length-to-height ratio of the beams prevents the proper formation of flexural plastic joints proposed by the regulations. Therefore, a frame with a single story and span has been proposed here consisting of a replaceable shear link made of shape memory alloy (SMA) to study the responses of the structure under the explosive loads (i.e., lateral loading) that can occur due to terrorist attacks, industrialization, or mining actions. Therefore, this study investigates the behavior of different systems under the three types of impact loads, including SMA or steel shear links. The results show that in the frame equipped with a shear link made of an SMA, the base shear is less than that of ordinary steel (the maximum base shear reduction is about 27% for type 2 blast load). This leads to a reduction in the cost of foundation construction. Also, the maximum displacement in the frame equipped with the shear link made of ordinary steel is less than the corresponding value in the frame equipped with a shear link made of an SMA (the maximum displacement reduction is about 43% for type 1 blast load), while the residual displacement of both frames is the same and equal to zero. It was concluded that the free vibration does not significantly affect the maximum responses of the mentioned structures under the impact load.